2021
DOI: 10.1186/s12941-021-00457-4
|View full text |Cite
|
Sign up to set email alerts
|

Virulence characterization and clonal analysis of uropathogenic Escherichia coli metallo-beta-lactamase-producing isolates

Abstract: Background Uropathogenic Escherichia coli (UPEC) is a major cause of urinary tract infection (UTI); however, treatment of UTI has been challenging due to increased antimicrobial resistance (AMR). One of the most important types of AMR is carbapenem resistance (CR). CR bacteria are known as an important threat to global public health today. Class B metallo-beta-lactamases (MBLs) are one of the major factors for resistance against carbapenems. We aimed to investigate the characteristics of UPEC i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…e most susceptible antibiotic was amikacin 84.2%. A comparable form of susceptibility to antibiotics was described against uropathogenic E. coli isolates in previous studies from Iran [31][32][33], and Iraq [34]. Based on what we learned, nitrofurantoin and amikacin seem to be good antibiotics for treating UPEC-related UTIs.…”
Section: Discussionsupporting
confidence: 73%
“…e most susceptible antibiotic was amikacin 84.2%. A comparable form of susceptibility to antibiotics was described against uropathogenic E. coli isolates in previous studies from Iran [31][32][33], and Iraq [34]. Based on what we learned, nitrofurantoin and amikacin seem to be good antibiotics for treating UPEC-related UTIs.…”
Section: Discussionsupporting
confidence: 73%
“…In a recent study from southwest Iran, each of bla IMP-1 and bla IMP-2 genes were detected in 8.3% of uropathogeneic E. coli isolates, while the bla NDM was detected in 75.0% of isolates. Also, the bla VIM-1 and bla VIM-2 were not detected [ 51 ]. In another study by Deldar Abad Paskeh et al [ 52 ] from Iran, a lower occurrence rates of bla IMP (8.7%) and bla VIM (9.8%) genes were reported in UTI-causing E. coli compared to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…21,28,29 Moreover, according to different studies conducted in Iran, ampicillin resistance can reach up to 80%, while resistance to SXT and ciprofloxacin was found in similar ranges to those found in our study (from 45 to 61%). 24,[30][31][32][33] In contrast, Allami et al found a different antibiotic resistance pattern, with SXT resistance of 87%, nitrofurantoin resistance of 45%, and ciprofloxacin resistance of 27%, while antibiotics such as amikacin and imipenem had low resistance (11% and 5%, respectively). 7 Also, a study conducted in Cameroon in 2012 showed how the pattern of antibiotic resistance changes even between cities in the same country.…”
Section: Antibiotic Resistance In Upec Strainsmentioning
confidence: 96%